KONTRIBUSI PERHATIAN ORANG TUA DALAM MEMOTIVASI TANGGUNG JAWAB BELAJAR ANAK DI SEKOLAH DASAR NEGERI - Tiwi Alawiyah; Afridha Sesrita (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2022)
Parents have an essential role in the development of children's learning. The part of parents is becoming increasingly visible while changing learning patterns during the COVID-19 pandemic because children as students experience several new problems, including the stability of their sense of learning responsibility. This study aims to determine the importance of giving parents attention to their children's sense of responsibility for learning, especially during the COVID-19 pandemic. The approach taken with the quantitative approach is a simple type of correlation research. This study involved students totaling 81 respondents who sat in class V. Questionnaire is a data collection technique used in this study. This study obtained the result that the value of r calculated by 0.634 and compared with the value of r table df 79 is 0.218. The value of r calculates > r table or 0.634 > 0.218, and the results show a relationship between parental attention and student learning responsibilities. This study can conclude; namely, there is a significant relationship between attention parents and the responsibility responsibility of student learning at SDN Tugu Selatan 02 Cisarua District Bogor Regency, West Java.